Analysis of Satisfaction Levels of Patients on Service Quality with The Importance Performance Analysis (IPA) Method - Vidyanto Vidyanto; Brigita Natasya Bertus; Sendhy Krisnasari; Muhammad Ryman Napirah (Media Publikasi Cendekia Indonesia, 2023)
The Importance Performance Analysis (IPA) method is a survey method that can be used to measure the satisfaction performance that is considered important by customers (expectations) and the satisfaction performance received by customers (reality). This research aims to determine the level of compatibility between performance and expectations of satisfaction towards the quality of service at the Biromaru Public Health Center in Sigi Regency. This type of research was quantitative with descriptive analysis techniques; the sample size used the Slovin formula, while the sampling used accidental sampling techniques. The total sample was 99 respondents. Data were collected through questionnaires and then analyzed using the Importance Performance Analysis (IPA) method. Results show that The Biromaru Public Health Center has met patient expectations in terms of the friendliness and politeness of health workers, the cleanliness of examination rooms, and the timeliness of doctor examinations. However, there are several areas where the health center can improve, such as the cleanliness and maintenance of the building, the waiting time for medicines, and the availability of sophisticated and adequate health facilities. The attributes that patients consider less important, but are still implemented well, include the appearance of health workers, the clarity of drug dosage information, and the good communication of nurses. The Bureaumaru Health Center has met patient expectations in terms of the courtesy and politeness of health workers, the cleanliness of the examination room, and the timeliness of doctor's examinations.